Edukasi Bahaya Pada Pangan Untuk Meningkatkan Kualitas Kesehatan Masyarakat Di Desa Karangjompo - Khusna Santika Rahmasari; Dwi Bagus Pambudi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Food safety is something that must be considered because it has an impact on human health. The lack of information and knowledge about food that is safe for consumption and the negative impact of food containing hazardous materials causes there are still many cases of food poisoning. This community service activity aims to provide education regarding the dangers of food to health in order to improve the health quality of the people of Karangjompo Village, Tirto District, Pekalongan Regency.The method of implementing this community service activity is to provide education in the form of counseling. Knowledge and experience in the food sector are expected to provide implications for food safety such as halal, healthy, clean, and nutritionally balanced food. The result of this community service activity is an increase in knowledge about food hazards by 13.22%.